Incidence and Radiological Predictors of Concomitant Meniscal and Cruciate Ligament Injuries in Operative Tibial Plateau Fractures: A Prospective Diagnostic Study - Chang, Hengrui; Zheng, Zhanle; Shao, Decheng; Yu, Yiyang; Hou, Zhiyong; Zhang, Yingze (Scientific reports, 2018)
The aim of this prospective study was to determine the incidence of meniscal and cruciate ligament injuries in operative tibial plateau fractures detected using knee arthroscopy, and to identify the radiological predictors observed on CT images. From January 2016 to February 2017, a total of 102 closed tibial plateau fractures were enrolled in this prospective protocol. Each patient underwent arthroscopic examination following the tibial plateau internal fixation. Univariate analysis and multivariable logistic regression were used to assess the association between imaging parameters and soft-tissue injuries. The menisci were traumatically injured in 52.9% of subjects (54 of 102) and the cruciate ligaments injured in 22.5% (23 of 102). Significantly higher injury rates for bucket-handle meniscal tears were observed in Schatzker type VI fractures ( P = 0.04). Greater risk of lateral meniscus injury was observed in patients with >6.3 mm of lateral joint depression. Greater risk of ACL injury when the volumetric lateral joint depression was ≤209.5 mm 2 and/or with >5.7 mm lateral joint widening. Associated meniscal and ligament injuries were commonly seen among operative tibial plateau fractures. Preoperative CT measurements might help predict a higher risk of meniscus and ACL injury, providing guidance to the surgeon to look for and to be prepared to treat such injuries.